2021
DOI: 10.57110/jeb.v1i5.4702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Small Business Households: A Case Study of Thanh Hoa and Tuyen Quang Provinces, Vietnam

Abstract: This study aims to assess the impact of COVID-19 on the business activities of 196 small business households, and their adaptation strategies to cope with those impacts in Thanh Hoa and Tuyen Quang provinces of Vietnam. By utilizing descriptive statistics and OLS regression, this study’s results show that all targeted business owners believe that COVID-19 had changed customer demands and reduced their supply input significantly. Our study findings also revealed that due to COVID-19, households’ living expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the case of China, the combined approaches (ordinary least squares [OLS] and ordered probit regression) employed by Yue et al (2021) indicate that the COVID-19 pandemic negatively impacted the gross income of household-owned businesses, and these small businesses struggled to survive as a result of the income losses sustained during the pandemic. Considering a sample of 196 household businesses in Thanh Hoa and Tuyen Quang provinces in Vietnam, Huong et al (2021) used OLS regression. They found that the COVID-19 pandemic significantly increased households' living expenditures, transportation costs, and input costs while decreasing the number of customers.…”
Section: Studies On Covid-19 and Household Entrepreneurshipmentioning
confidence: 99%
“…In the case of China, the combined approaches (ordinary least squares [OLS] and ordered probit regression) employed by Yue et al (2021) indicate that the COVID-19 pandemic negatively impacted the gross income of household-owned businesses, and these small businesses struggled to survive as a result of the income losses sustained during the pandemic. Considering a sample of 196 household businesses in Thanh Hoa and Tuyen Quang provinces in Vietnam, Huong et al (2021) used OLS regression. They found that the COVID-19 pandemic significantly increased households' living expenditures, transportation costs, and input costs while decreasing the number of customers.…”
Section: Studies On Covid-19 and Household Entrepreneurshipmentioning
confidence: 99%